2016
DOI: 10.12968/bjon.2016.25.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Working towards widening participation in nurse education

Abstract: The widening participation agenda has particular significance for worldwide nursing since it is a profession which is under increasing scrutiny in its recruitment and retention practices. Debate about this agenda within nurse education is strengthened by careful scrutiny of the research within the wider context of higher education, some of which challenges commonly held assumptions. This paper examines four areas of relevance to the UK widening participation agenda: disability, ethnicity, socioeconomic status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…This study explored the views of UK 'home grown' South Asian prospective students on choosing NHS funded nursing and midwifery courses and careers. In common with other studies our research findings identified a number of barriers for South Asian people [18,37]. Personal, parental and South Asian community misconceptions about nursing specialisms and roles perceptions of low incomes, long working hours, shift work and poor career progression was influencing ideas about nursing and midwifery as a low status profession [19,9].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study explored the views of UK 'home grown' South Asian prospective students on choosing NHS funded nursing and midwifery courses and careers. In common with other studies our research findings identified a number of barriers for South Asian people [18,37]. Personal, parental and South Asian community misconceptions about nursing specialisms and roles perceptions of low incomes, long working hours, shift work and poor career progression was influencing ideas about nursing and midwifery as a low status profession [19,9].…”
Section: Discussionsupporting
confidence: 82%
“…Studies looking specifically at the views and experiences of South Asians have found that nursing is perceived as being women's work, is poorly paid, and involves working night shifts and providing physical care to the opposite sex which is religiously and culturally unacceptable. These studies also report tensions and difficulties in academic life, lack of exposure to positive role models and poor knowledge of nursing career structure [17,36,37].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…In Australia, over half of all students enrolled in nursing degrees are nonschool leavers (Australian Bureau of Statistics, ) with a similar picture in the UK, where a quarter of all commencing students are over 30 years of age (Keogh, ). Such students are more likely to have family responsibilities, increased financial commitments and a heightened need to undertake paid work (Keogh, ; Young, ).…”
Section: Introductionmentioning
confidence: 99%
“…Commonly referred to as “widening participation,” reforms including flexible admission policies, recognition of prior education and the adoption of new teaching methods have provided the opportunity for nontraditional students to pursue a university education (Drury, Francis, & Chapman, ). As a result, universities are experiencing increasing enrolments of students from traditionally under‐represented groups, including mature age students, those with disabilities, students from ethnically diverse backgrounds, as well as students from low socioeconomic status backgrounds (Young, ). Within this context, necessity compels many of these students to engage in significant amounts of paid employment while studying full time.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, universities are experiencing increasing enrolments of students from traditionally under-represented groups, including mature age students, those with disabilities, students from ethnically diverse backgrounds, as well as students from low socioeconomic status backgrounds (Young, 2016). Within this context, necessity compels many of these students to engage in significant amounts of paid employment while studying full time.…”
Section: Introductionmentioning
confidence: 99%